Physical Activity and Blood Pressure Changes in Pre-Elderly Adults: Evidence from the Prolanis Program at Bumirejo Community Health Center - kholifah hasnah; Amir Ramadhani A N (Journal of Indonesian Anesthesiology Nursing, 2025)
Background: Physical activity is the body movement produced by skeletal muscle and requires energy expenditure. One of the factors that affect blood pressure is physical activity. Increased blood pressure regulated by the reticular activation system in the brain stem will stimulate the area of ​​the vasoconstrictor and the cardioaccelerator at the vasomotor center. The purpose of this study is to know the relationship between physical activity and blood pressure changes on pre-elderly people in Prolanis Puskesmas Bumirejo. Methods: This study is a descriptive correlative is to examine the relationship between variables. The sample in this study was all pre-elderly people in Prolanis Puskesmas Bumirejo totally 45 people. Sampling technique used was purposive sampling. It was conducted in Prolanis Puskesmas Bumirejo. The study was taken during April to May 2018. Data analysis was executed using Spearman Rank statistical test. Results: Based on the results of the study, it is known that respondents’ characteristics of the pre-elderly people in Prolanis Puskesmas Bumirejo mostly are men whose age are between 45-55 years old with the last education level of junior high school. Physical activity in pre-elderly people in Prolanis Puskesmas Bumirejo is known that most of them are in high category (46,7%). Blood pressure in pre-elderly people in Prolanis Puskesmas Bumirejo is known that mostly included in normal category (40,0%). There is an association between physical activity with blood pressure changes on pre-elderly peoplein Prolanis Puskesmas Bumirejo (p = 0,000). Conclusion: This research concludes that there is a relationship between physical activity and blood pressurechanges on pre-elderly peoplein Prolanis Puskesmas Bumirejo